Respuesta :

Here’s my answer, hope it’s right:
Ver imagen Neptune364

Answer:

[tex]B = \frac{6D + 18 {f}^{3} }{M} [/tex]

Step-by-step explanation:

[tex] - 3 {f}^{3} + \frac{1}{6} MB = D [/tex]

Multiply through by 6 to eliminate the fraction

That's

[tex] - 18 {f}^{3} + MB = 6D[/tex]

Move - 18f³ to the right side of the equation

That's

[tex]MB = 6D + 18 {f}^{3} [/tex]

Divide both sides by M to make B stand alone

That's

[tex] \frac{MB}{M} = \frac{6D + 18 {f}^{3} }{M} [/tex]

We have the final answer as

[tex]B = \frac{6D + 18 {f}^{3} }{M} [/tex]

Hope this helps you